Impact of Dysprosium doping on the structural and electrical properties of BiSbTe3 single crystals. (2022) - Yadav, Nisha; Anoop, M.D.; Yadav, Jyoti; Singh, Rini; Bera, Nabarun; Jain, Ankur; Ichikawa, Takayuki; Awasthi, Kamlendra; Kumar, Manoj
Highlights: Undoped and Dy doped BiSbTe3 single crystals were grown. The resistivity was increased with rare earth doping suggesting the incorporation of defects with doping. The T2 dependence suggests the Fermi liquid behaviour of samples. The Hall measurements revealed that holes are the dominant charge carriers. The Hall measurements demonstrates that Fermi level is shifted with Dy doping and is very close to Dirac point as the concentration of Dy is increased. Abstract: Breaking of time reversal symmetry in 3D topological insulators and tuning of Fermi level in the vicinity of the Dirac point is a prerequisite for unravelling various exotic physical phenomena which might be leveraged for potential technological device applications. Here we account effective single crystal growth of (BiSb)2-x Dyx Te3 where x = 0, 0.005, 0.05 using modified Bridgman method. The structural, morphological, electrical and Hall measurements were performed on the synthesized single crystals. X-ray Diffraction (XRD) measurements confirmed high quality crystal growth with unidirectional orientation of the synthesized crystals. The lattice parameters were found decreasing with Dysprosium (Dy) doping thereby decreasing the lattice volume, indicating the incorporation of Dy atoms in the lattice of BiSbTe3 . Scanning Electron Microscopy (SEM) confirmed the layered morphology of synthesized crystals while Energy Dispersive X-ray Spectroscopy (EDX) measurements revealed the uniform distribution of all the elements as well as stoichiometry of prepared crystals. The resistivity versus temperature (ρ-T) plot from 4 K to 300 K showed metallic behaviour of crystals with an increase in resistivity with Dy doping. The Hall resistivity (ρxy ) demonstrates that holes are the predominant charge carriers. The Hall data revealed displacement of Fermi level with Dy doping. These results are indicative to the shift in the Fermi level in the vicinity of the Dirac point.